Foundation owned firms - a delegation approach - Stefan Mühlbauer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Foundation owned firms are an interesting research object to test ownership influence on firms' performance. Research claims that the foundation as an organization without natural owner leads to significant agency cost because there is no residual claimant with an incentive to control. Nevertheless, this inferior performance could not be found empirically (Herrmann (1997), Thomsen (1999), Thomsen (2004)). This paper gives an explanation for this puzzling result: most foundation owned firms are not as owner-less as it seems. The presented model is the first to analyse game theoretically a firm succession decision with the option to choose a foundation as successor, a form of succession very popular in Central and Northern Europe. More precisely the succession decision is analysed in a delegation model by Holmstrom (1977) and Melumad & Shibano (1991). It is assumed that the founder can either pass his firm on to his successor or donate his firm to a foundation. It is shown that a foundation as successor can be rational, as, by setting it up and designing it, the founder can restrict the successors discretion and therefore can prevent specific events from happening, for example the sale of his firm. The model illustrates the basic trade-off a founder faces. In order to keep control he has to sacrifices adaptability of future management. The founder leaves his successor as actual owner despite donating it to a foundation. This could explain the many ways how foundations and firms are legally arranged in Germany and could have important implications for future empirical research on foundation owned firms.
Keywords: L25; L21; M12; 330